Distribution of gall crabs inhabiting mushroom corals on Semporna reefs, Malaysia - van der Meij, S; Hoeksema, B (Springer-Verlag Berlin Heidelberg, 2013)
Coral reef cryptofauna forms an important component of tropical marine biodiversity, consisting primarily of invertebrates dwelling in and on corals. During a survey carried out around the Semporna peninsula (Sabah, NE Borneo), the occurrence of gall crabs inhabiting mushroom corals was examined on reefs ranging from sheltered to exposed conditions. Out of 44 fungiid species, 19 were found to be associated with gall crabs. The gall crabs were observed at 85 % of the 62 studied sites, and their occurrence rates per site ranged between 0 and 25 %. High occupancy rates were almost equally distributed over the northern (sheltered) and southern (exposed) sites. Sites without gall crabs were all wave-exposed and predominantly under the influence of disturbances, such as blast fishing or relatively high nutrient loads. © 2012 Senckenberg Gesellschaft für Naturforschung and Springer-Verlag Berlin Heidelberg.